2008
DOI: 10.1159/000151441
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Adherence to Treatment and Quality of Life in Mild to Moderate Acne

Abstract: Background: Adherence to treatment is a mayor issue in dermatology, and its relationship to quality of life has barely been studied. Objective: To evaluate the relationship between scores on the Skindex-29 skin disease assessment scale and adherence to treatment in patients with acne. Methods: An observational, prospective study of 1,628 patients carried out by 252 clinicians in Spain. Results: Adherence was related to better objective and subjective severity index scores and better Skindex-29 scale scores at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 46 publications
4
46
0
1
Order By: Relevance
“…This is in accordance to a previous study using a 5-point Likert PGA scale9. This has also been shown in a variety of other disease states, including acne, pemphigus, psoriasis, cutaneous lupus, and vitiligo10, 4042, 51,5.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance to a previous study using a 5-point Likert PGA scale9. This has also been shown in a variety of other disease states, including acne, pemphigus, psoriasis, cutaneous lupus, and vitiligo10, 4042, 51,5.…”
Section: Discussionsupporting
confidence: 92%
“…Adherence to treatment has been linked to better outcomes in acne and improvement of Quality of Life. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Dreno et al [4] also found a risk of poor adherence of 60% among patients taking a combination of both systemic and topical therapy, and a higher likelihood of poor adherence to the systemic arm of treatment compared to the topical arm (54 vs. 44%, respectively). Other studies utilizing questionnaires and/or single questions to assess adherence have found rates of poor adherence ranging from 76 to 0% [2,3,5,15,16,17]. Studies using objective measures such as not keeping appointments, pill counts, weighing medication, number of medication refills, and electronic caps have reported adherence rates ranging from 28 to 88.3% [6,7,8,18].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated adherence to acne medications in various parts of the world [2,3,4,5,6,7,8]; however, there are few data specific to Japan. This study was designed to assess adherence among acne patients in Japan, to determine if there are differences in adherence based on type of treatment (topical or oral), and to evaluate the factors that can affect adherence to acne treatment.…”
Section: Introductionmentioning
confidence: 99%